Steel sheet and method for manufacturing the same
Patent Information
- Application Number
- CN202280055067.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-31
- Filing Date
- 2022-03-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-03-31
AI Technical Summary
然而,在现有技术中,虽然对高强度钢板的加工性等进行了研究(例如以下的专利文献1~3),但对于确保对来自表背面两侧的弯曲变形的耐弯承受力并没有进行充分的研究
[0095]本公开的钢板的强度、伸长率等机械特性优异,并且耐弯承受力也优异。
Smart Images

Figure BDA0004700257690000311 
Figure BDA0004700257690000321 
Figure BDA0004700257690000331
Abstract
Description
Technical Field
[0001] This application discloses a steel plate and a method for manufacturing the same. Background Technology
[0002] In recent years, efforts have been made to improve fuel efficiency in automobiles, leading to lighter vehicle bodies through the application of high-strength steel. Furthermore, to ensure passenger safety, high-strength steel is increasingly being used in vehicle bodies to replace mild steel. Going forward, to further advance vehicle body lightweighting, the strength level of high-strength steel must be increased to a level far exceeding previous levels.
[0003] Furthermore, automotive components are required to function in suppressing deformation during a vehicle collision. To improve the resistance of automotive components to deformation in a collision, it is desirable to improve their bending resistance. Moreover, to enhance bending resistance from a structural perspective through appropriate component shape, high formability of the steel sheet is required. Therefore, steel sheets used in automotive components are required to be high-strength, possess excellent bending resistance, and exhibit higher elongation. However, while prior art has investigated the processability of high-strength steel sheets (for example, see Patent Documents 1-3 below), sufficient research has not been conducted on ensuring bending resistance against bending deformation from both the front and back sides.
[0004] In Patent Document 1, a high-strength steel plate with excellent workability is disclosed, which has ferrite as the main phase, contains an average of more than 5% by volume of retained austenite, and the difference between the maximum and minimum retained austenite content at each position in the thickness direction between 0.1 mm from the surface of the steel plate and 0.1 mm from the back of the steel plate is less than 3.0% by volume.
[0005] Patent Document 2 discloses a steel plate with excellent shock absorption capacity that minimizes damage to the hull during a collision with an oil tanker. The steel plate is characterized by having a thickness of 8 mm or more and containing C, Si, Mn, Al, and further, reinforcing elements as needed, with the remainder consisting of Fe and unavoidable impurities. The steel plate contains 1.0 to 20% residual γ in the surface and back layers, which are at least 1 / 8 of the plate thickness.
[0006] Patent document 3 discloses a steel plate for structural use that can simultaneously and dramatically improve the brittle crack propagation cessation characteristics and Charpy characteristics without relying on the addition of expensive alloying elements such as Ni. The steel plate is composed of the following weight percentages: C: 0.04-0.30%, Si: ≤0.5%, Mn: ≤2.0%, Al: ≤0.1%, Ti: 0.001-0.10%, N: 0.001-0.01%, with the remainder consisting of Fe and unavoidable impurities. The average grain size d of the microstructure in a specified region of the plate thickness surface layer is 3 μm or less, and the Vickers hardness of the microstructure meets the specified necessary conditions.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent No. 3546266
[0010] Patent Document 2: Japanese Patent No. 3499126
[0011] Patent Document 3: Japanese Patent No. 3845113 Summary of the Invention
[0012] The problem that the invention aims to solve
[0013] In view of the above facts, this application discloses a steel plate with excellent mechanical properties such as strength and elongation and excellent bending resistance, and a method for manufacturing the same.
[0014] Methods for solving problems
[0015] The inventors of this invention conducted in-depth research on methods to solve the aforementioned problems and clarified that by optimizing the proportion of the steel sheet microstructure, represented by retained austenite, and reducing the difference in the number density of precipitates on the front and back surfaces, steel sheets with excellent mechanical properties such as strength and elongation, and exhibiting high bending resistance, can be obtained. They also confirmed that for steel sheets with a difference of more than 10% in the number density of precipitates on the front and back surfaces, the bending resistance varies depending on the direction of bending, and the deformation resistance (deformation drag) of the component during impact occasionally decreases.
[0016] Furthermore, the inventors of this invention have discovered that a steel sheet with optimized microstructure and a small difference in the number density of precipitates on the front and back sides can be manufactured by the following continuous manufacturing method, characterized in that the cold-rolled sheet is subjected to two annealing processes, and between the two annealing processes, the steel sheet is coiled and uncoiled to perform a prescribed aging treatment.
[0017] Furthermore, the inventors of this invention have realized through repeated research that it is difficult to manufacture steel plates with improved bending strength by reducing the difference in the number density of precipitates on the front and back surfaces, even by simply focusing on hot rolling conditions and annealing conditions. It is only possible to manufacture them by optimizing a so-called continuous process, such as hot rolling and annealing.
[0018] The main points of this invention are as follows.
[0019] (1) A steel plate having the following chemical composition: containing, by mass %:
[0020] C: 0.10~0.30%
[0021] Si: 0.60–1.20%
[0022] Mn: 1.00~3.50%
[0023] P: below 0.0200%
[0024] S: Below 0.0200%
[0025] Al: 0.001~1.000%
[0026] N: below 0.0200%
[0027] Ti: 0~0.500%
[0028] Co: 0~0.500%
[0029] Ni: 0~0.500%
[0030] Mo: 0–0.500%
[0031] Cr: 0–2.000%
[0032] O: 0~0.0100%
[0033] B: 0~0.0100%
[0034] Nb: 0~0.500%
[0035] V: 0~0.500%
[0036] Cu: 0~0.500%
[0037] W: 0~0.1000%
[0038] Ta: 0~0.1000%
[0039] Sn: 0~0.0500%
[0040] Sb: 0~0.0500%
[0041] As: 0~0.0500%
[0042] Mg: 0~0.0500%
[0043] Ca: 0~0.0500%
[0044] Y: 0~0.0500%
[0045] Zr: 0~0.0500%
[0046] La: 0~0.0500%, and
[0047] Ce: 0~0.0500%
[0048] The remaining part consists of Fe and impurities.
[0049] The steel plate has the following steel structure, comprising, in terms of area ratio:
[0050] The total content of ferrite, pearlite, and bainite: 0%–30.0%, and
[0051] Residual austenite: 10.0%–30.0%
[0052] The remaining portion is formed from primary martensite and tempered martensite.
[0053] The difference between the number density of precipitates in the tempered martensite on the first surface of the steel plate and the number density of precipitates in the tempered martensite on the second back surface of the steel plate is within 10.0%.
[0054] The yield strength of the steel plate is above 600 MPa.
[0055] (2) The steel plate according to (1) above has a chemical composition containing one or more of the following elements in a mass percentage:
[0056] Ti: 0.001~0.500%
[0057] Co: 0.001~0.500%
[0058] Ni: 0.001~0.500%
[0059] Mo: 0.001~0.500%
[0060] Cr: 0.001~2.000%
[0061] O: 0.0001~0.0100%
[0062] B: 0.0001~0.0100%
[0063] Nb: 0.001~0.500%
[0064] V: 0.001~0.500%
[0065] Cu: 0.001~0.500%
[0066] W: 0.0001~0.1000%
[0067] Ta: 0.0001~0.1000%
[0068] Sn: 0.0001~0.0500%
[0069] Sb: 0.0001~0.0500%
[0070] As: 0.0001~0.0500%
[0071] Mg: 0.0001~0.0500%
[0072] Ca: 0.0001~0.0500%
[0073] Y: 0.0001~0.0500%
[0074] Zr: 0.0001~0.0500%
[0075] La: 0.0001~0.0500%, and
[0076] Ce: 0.0001~0.0500%.
[0077] (3) The steel plate according to (1) or (2) above, wherein,
[0078] The aforementioned steel microstructure contains needle-like residual austenite.
[0079] (4) A method for manufacturing a steel plate, comprising the following steps:
[0080] A hot-rolled plate is obtained by hot rolling a steel slab having the chemical composition described in (1) or (2) above;
[0081] The hot-rolled sheet is then coiled.
[0082] The hot-rolled plates were pickled.
[0083] The above-mentioned hot-rolled sheet is cold-rolled to obtain a cold-rolled sheet;
[0084] The above-mentioned cold-rolled sheet was subjected to Q annealing (Q: quenching).
[0085] The cold-rolled sheet subjected to the above Q annealing is then subjected to IA annealing (IA: Intercritical Annealing); and
[0086] An aging process is performed between the Q-annealing and the IA-annealing described above.
[0087] The Q annealing described above is a process in which the cold-rolled sheet is heated to a temperature below 1000°C in the austenitic single-phase region and then cooled to obtain a martensitic structure with an area fraction of 90.0% or more.
[0088] The aforementioned IA annealing is a process in which the cold-rolled sheet is held in a two-phase region of ferrite and austenite to obtain retained austenite.
[0089] The aforementioned aging treatment includes: aging treatment 1, which maintains the state in which one of the front and back sides of the cold-rolled sheet is subjected to tensile deformation with a bending radius of less than 2.0m at 0 to 40°C for a period of 20 hours or more; and aging treatment 2, which maintains the state in which the other side of the front and back sides of the cold-rolled sheet is subjected to tensile deformation with a bending radius of less than 2.0m at 0 to 40°C for a period of 20 hours or more.
[0090] (5) The manufacturing method according to (4) above, wherein,
[0091] In the aforementioned IA annealing, after the cold-rolled sheet is held in the two-phase region of ferrite and austenite and then cooled to room temperature, a coating layer containing zinc, aluminum, magnesium, or alloys thereof is formed on the front and back surfaces of the cold-rolled sheet.
[0092] (6) The manufacturing method according to (4) or (5), wherein,
[0093] In the above-mentioned IA annealing, needle-like residual austenite is obtained.
[0094] Invention Effects
[0095] The steel plate disclosed herein has excellent mechanical properties such as strength and elongation, and also excellent bending resistance. Detailed Implementation
[0096] The embodiments of the present invention will be described below. It should be noted that these descriptions are merely illustrative of the embodiments of the present invention, and the present invention is not limited to the following embodiments.
[0097] <steel plate>
[0098] The steel plate of this embodiment is characterized by having the following chemical composition: containing, by mass %:
[0099] C: 0.10~0.30%
[0100] Si: 0.60–1.20%
[0101] Mn: 1.00~3.50%
[0102] P: below 0.0200%
[0103] S: Below 0.0200%
[0104] Al: 0.001~1.000%
[0105] N: below 0.0200%
[0106] Ti: 0~0.500%
[0107] Co: 0~0.500%
[0108] Ni: 0~0.500%
[0109] Mo: 0–0.500%
[0110] Cr: 0–2.000%
[0111] O: 0~0.0100%
[0112] B: 0~0.0100%
[0113] Nb: 0~0.500%
[0114] V: 0~0.500%
[0115] Cu: 0~0.500%
[0116] W: 0~0.1000%
[0117] Ta: 0~0.1000%
[0118] Sn: 0~0.0500%
[0119] Sb: 0~0.0500%
[0120] As: 0~0.0500%
[0121] Mg: 0~0.0500%
[0122] Ca: 0~0.0500%
[0123] Y: 0~0.0500%
[0124] Zr: 0~0.0500%
[0125] La: 0~0.0500%, and
[0126] Ce: 0~0.0500%
[0127] The remaining part consists of Fe and impurities.
[0128] The steel plate has the following steel structure, comprising, in terms of area ratio:
[0129] The total content of ferrite, pearlite, and bainite: 0%–30.0%, and
[0130] Residual austenite: 10.0%–30.0%
[0131] The remaining portion is formed from primary martensite and tempered martensite.
[0132] The difference between the number density of precipitates in the tempered martensite on the first surface of the steel plate and the number density of precipitates in the tempered martensite on the second back surface of the steel plate is within 10.0%.
[0133] The yield strength of the steel plate is above 600 MPa.
[0134] First, the reasons for defining the chemical composition of the steel plate according to the embodiments of the present invention will be explained. Here, the "%" of the composition refers to "mass %". Furthermore, in this specification, the "~" indicating a numerical range is used to mean the lower limit and upper limit of the values described before and after it unless otherwise specified.
[0135] (C: 0.10~0.30%)
[0136] Carbon (C) is an inexpensive element that increases tensile strength and is extremely important for controlling the strength of steel. This effect is easily achieved when the C content is above 0.10%, and can also be above 0.12%. On the other hand, excessive C content can reduce elongation and lead to brittle fracture of the steel, promoting a decrease in the bending resistance of the component during deformation. These problems are easily avoided when the C content is below 0.30%, and can also be below 0.28%.
[0137] (Si: 0.60~1.20%)
[0138] Si acts as a deoxidizer, improving the stability of the retained austenite structure during processing and inhibiting the precipitation of carbides in the martensite structure during aging. This effect is easily achieved when the Si content is 0.60% or higher. The Si content can also be 0.70% or higher. On the other hand, excessive Si content may inhibit the formation of ε-carbides during aging, reducing flexural strength. This problem is easily avoided when the Si content is 1.20% or lower. The Si content can also be 1.00% or lower.
[0139] (Mn: 1.00~3.50%)
[0140] Mn is a factor that affects the ferrite phase transformation of steel. It is an element that inhibits the ferrite phase transformation during the cooling process of Q annealing (described later), increases the martensite ratio after Q annealing, and is effective in increasing strength. This effect is easily obtained when the Mn content is 1.00% or higher. The Mn content can also be 1.30% or higher. On the other hand, if the Mn content is excessive, a Mn-concentrated layer formed by microsegregation and central segregation will be significantly observed in the steel sheet. Due to the difference in solidification rate between the front and back sides of the slab, the distribution of the Mn-concentrated layer on the front and back sides of the steel sheet will differ, which may cause differences in the bending strength of the front and back sides due to the difference in the formation of Mn segregation bands. This problem is easily avoided when the Mn content is 3.50% or lower. The Mn content can also be 3.00% or lower.
[0141] (P: below 0.0200%)
[0142] Phosphorus (P) is an element that strongly segregates at ferrite grain boundaries, promoting grain boundary embrittlement; therefore, a lower content is preferred. Furthermore, excessive P content can lead to brittle fracture in steel and reduce the bending strength of components during deformation. In this regard, the P content is 0.0200% or less. The P content can also be 0.0180% or less. On the other hand, there is no particular limitation on the lower limit of the P content. The P content can be 0% or more, or it can be 0.0001% or more, or it can be 0.0010% or more.
[0143] (S: below 0.0200%)
[0144] Sulfur (S) is an element that forms non-metallic inclusions such as MnS in steel, reducing the ductility of steel components; a lower content is preferred. Furthermore, excessive S content can lead to the formation of voids originating from non-metallic inclusions during component deformation, thus reducing bending resistance. In this regard, an S content of 0.0200% or less is preferred. An S content of 0.0180% or less is also acceptable. On the other hand, there is no particular limitation on the lower limit of S content. An S content of 0% or more, or 0.0001% or more, or 0.0005% or more is acceptable.
[0145] (Al: 0.001~1.000%)
[0146] Al acts as a deoxidizer in steel, stabilizing ferrite, and is added as needed. This effect is easily achieved when the Al content is 0.001% or higher. The Al content can also be 0.010% or higher. On the other hand, excessive Al content may excessively promote ferrite and bainite phase transformations during cooling in annealing, thus reducing the strength of the steel sheet. This problem is easily avoided when the Al content is 1.000% or lower. The Al content can also be 0.800% or lower.
[0147] (N: below 0.0200%)
[0148] Nitrogen (N) is an element that forms large nitrides in steel sheets, reducing their machinability. Furthermore, N contributes to porosity during welding. Excessive N content can combine with Al and Ti to form large amounts of AlN or TiN; these nitrides become the starting point for void formation during component deformation, leading to reduced bending strength. In this regard, the N content is 0.0200% or less. The N content can also be 0.0160% or less. On the other hand, there is no particular limitation on the lower limit of the N content. The N content can be 0% or more, or 0.0001% or more, or 0.0010% or more.
[0149] The basic chemical composition of the steel plate in this embodiment is as described above. Furthermore, the steel plate in this embodiment may, as needed, contain at least one of the following optional elements. Since these elements may also be omitted, the lower limit is 0%.
[0150] (Ti: 0~0.500%)
[0151] Ti is a strengthening element. It contributes to increased strength in steel sheets through precipitation strengthening, fine-grain strengthening due to inhibited grain growth, and dislocation strengthening through inhibited recrystallization. On the other hand, excessive Ti content can lead to the precipitation of coarse carbides, which can become the starting point for voids during component deformation, resulting in reduced bending resistance. Ti content can be 0% or more, or 0.001% or more, or 0.005% or more, and can also be 0.500% or less, or 0.400% or less.
[0152] (Co: 0-0.500%)
[0153] Co is an effective element for controlling the morphology of carbides and increasing strength, and is added as needed for strength control. On the other hand, if there is an excessive amount of Co, fine Co carbides may precipitate in large quantities. These carbides become the starting point for voids during component deformation, leading to a decrease in bending strength. The Co content can be 0% or more, or 0.001% or more, or 0.500% or less, or 0.400% or less.
[0154] (Ni: 0~0.500%)
[0155] Ni is a strengthening element and is effective in improving hardenability. Furthermore, it can be added to improve the wettability of the steel sheet and coating, and promote alloying reactions. On the other hand, excessive Ni content affects the peeling of oxide scale during hot rolling, promotes the formation of scratches on the steel sheet surface, and may therefore reduce the resistance to bending deformation. The Ni content can be 0% or more, or 0.001% or more, or 0.500% or less, or 0.400% or less.
[0156] (Mo: 0~0.500%)
[0157] Mo is an effective element for improving the strength of steel plates. Furthermore, Mo has the effect of suppressing the ferrite phase transformation that occurs during heat treatment using continuous annealing or continuous hot-dip galvanizing equipment. On the other hand, if the Mo content is excessive, a large amount of fine Mo carbides may precipitate, which become the starting point for void formation during component deformation, leading to a decrease in bending strength. The Mo content is 0% or more, or 0.001% or more, or 0.500% or less, or 0.400% or less.
[0158] (Cr: 0~2.000%)
[0159] Cr, like Mn, is an element that inhibits pearlite phase transformation and is effective in increasing the strength of steel; it is added as needed. On the other hand, excessive Cr content may promote the formation of retained austenite, leading to a decrease in flexural strength due to the presence of excessive retained austenite. The Cr content can be 0% or more, or 0.001% or more, or 2.000% or less, or 1.500% or less.
[0160] (O: 0~0.0100%)
[0161] O (O) forms oxides, which degrade processability, therefore its addition must be controlled. In particular, oxides often exist as inclusions; if present on the punched or cut surfaces, they can form notched marks and large dimples, potentially causing stress concentration during component deformation, becoming the starting point for crack formation, and leading to a reduction in bending strength. The O content can be 0.0100% or less, or even 0.0080% or less. It should be noted that while the O content is 0% or more, controlling it below 0.0001% may increase refining time and manufacturing costs. To prevent increased manufacturing costs, the O content can also be 0.0001% or more, or even 0.0010% or more.
[0162] (B: 0~0.0100%)
[0163] Boron (B) is an element that inhibits the formation of ferrite and pearlite during the cooling process from austenite, and promotes the formation of low-temperature phase transformation structures such as bainite or martensite. Furthermore, B is beneficial for increasing the strength of steel and is added as needed. On the other hand, excessive B content leads to the formation of large B inclusions in the steel. These inclusions become the starting point for void formation, potentially reducing the bending strength of the component during deformation. The B content can be 0% or more, or 0.0001% or more, or 0.0010% or less, or 0.0100% or less.
[0164] (Nb: 0~0.500%)
[0165] Nitrogen (Nb) is an effective element for controlling the morphology of carbides. Because its addition refines the microstructure, it is also effective in improving toughness. On the other hand, excessive Nb content leads to the precipitation of large amounts of fine and hard Nb carbides, which become the starting point for void formation, potentially reducing the bending strength of the component during deformation. The Nb content can be 0% or more, or 0.001% or more, or 0.500% or less, or 0.400% or less.
[0166] (V: 0~0.500%)
[0167] V is a strengthening element. It contributes to increased strength in steel sheets through precipitation strengthening, fine-grain strengthening due to inhibited ferrite grain growth, and dislocation strengthening through inhibited recrystallization. On the other hand, excessive V content leads to increased carbonitride precipitation, which becomes the starting point for void formation, potentially reducing the bending strength of components during deformation. V content can be 0% or more, or 0.001% or more, or 0.500% or less, or 0.400% or less.
[0168] (Cu: 0~0.500%)
[0169] Cu is an effective element for improving the strength of steel plates. On the other hand, if the Cu content is excessive, the steel becomes embrittled during hot rolling, making hot rolling difficult. Consequently, while the strength of the steel increases, its ductility decreases, which may lead to a reduction in the bending resistance of the component during deformation. The Cu content is 0% or more, or 0.001% or more, or 0.500% or less, or 0.400% or less.
[0170] (W: 0~0.1000%)
[0171] W is effective in increasing the strength of steel plates, and W-containing precipitates and crystals serve as hydrogen trapping sites. On the other hand, if the W content is excessive, the formation of voids, starting with coarse carbides, becomes easier, which may lead to a decrease in the bending resistance of the component during deformation. The W content can be 0% or more, or 0.0001% or more, or 0.0010% or more, or 0.1000% or less, or 0.0800% or less.
[0172] (Ta: 0~0.1000%)
[0173] Ta, like Nb, V, and W, is an element effective in controlling the morphology of carbides and increasing strength, and should be added as needed. On the other hand, if Ta is excessive, a large amount of fine Ta carbides will precipitate, and the formation of voids becomes easier with these carbides as a starting point, which may lead to a decrease in the bending resistance of the component during deformation. The Ta content can be 0% or more, or 0.0001% or more, or 0.0010% or less, or 0.1000% or less, or 0.0800% or less.
[0174] (Sn: 0~0.0500%)
[0175] Sn is an element contained in steel when using scrap as raw material, and a lower content is preferred. Excessive Sn content can lead to embrittlement of the steel plate, resulting in reduced bending strength of the component during deformation. Sn content can be below 0.0500% or even below 0.0400%. It should be noted that while Sn content can be 0%, controlling it below 0.0001% may increase refining time and manufacturing costs. To prevent increased manufacturing costs, Sn content can also be above 0.0001% or even above 0.0010%.
[0176] (Sb: 0~0.0500%)
[0177] Sb, like Sn, is an element present when scrap is used as raw material for steel. Sb causes strong segregation at grain boundaries, leading to grain boundary embrittlement and reduced ductility; therefore, a lower content is preferred. Furthermore, excessive Sb content can reduce the bending strength of components during deformation due to steel embrittlement. The Sb content can be 0.0500% or less, or even 0.0400% or less. It should be noted that while the Sb content can be 0%, controlling it below 0.0001% may increase refining time and manufacturing costs. To prevent increased manufacturing costs, the Sb content can also be 0.0001% or more, or even 0.0010% or more.
[0178] (As: 0~0.0500%)
[0179] As, like Sn and Sb, is an element that is present in steel made from scrap and strongly segregates at grain boundaries; a lower content is preferred. Furthermore, excessive As content can lead to embrittlement of the steel sheet, resulting in reduced bending strength during component deformation. The As content should be 0.0500% or less, or even 0.0400% or less. It should be noted that while the As content can be 0%, controlling it below 0.0001% may increase refining time and manufacturing costs. To prevent increased manufacturing costs, the As content can also be 0.0001% or more, or even 0.0010% or more.
[0180] (Mg: 0~0.0500%)
[0181] Mg is an element whose sulfide morphology can be controlled by adding trace amounts, and it is added as needed. On the other hand, if there is an excessive amount of Mg, coarse inclusions will form, which become the starting point for void formation, and may therefore lead to a decrease in the bending resistance of the component during deformation. The Mg content can be 0% or more, or 0.0001% or more, or 0.0010% or more, or 0.0500% or less, or 0.0400% or less.
[0182] (Ca: 0~0.0500%)
[0183] Ca is useful not only as a deoxidizing element but also in controlling the morphology of sulfides. On the other hand, excessive Ca content can lead to embrittlement of the steel plate, resulting in a decrease in the bending strength of the component during deformation. The Ca content can be 0% or more, or 0.0001% or more, or 0.0010% or more, or 0.0500% or less, or 0.0400% or less.
[0184] (Y: 0~0.0500%)
[0185] Y, like Mg and Ca, is an element whose sulfide morphology can be controlled by adding trace amounts, and it is added as needed. On the other hand, if there is an excessive amount of Y, coarse Y inclusions are formed, which become the starting point for void formation, and may therefore lead to a decrease in the bending resistance of the component during deformation. The Y content can be 0% or more, or 0.0001% or more, or 0.0010% or more, or 0.0500% or less, or 0.0400% or less.
[0186] (Zr: 0~0.0500%)
[0187] Zr, like Mg, Ca, and Y, is an element whose sulfide morphology can be controlled by adding it in trace amounts, and it should be added as needed. On the other hand, if there is an excessive amount of Zr, coarse Zr inclusions will be formed, which become the starting point for void formation and may therefore lead to a decrease in the bending resistance of the component during deformation. The Zr content can be 0% or more, or 0.0001% or more, or 0.0010% or more, or 0.0500% or less, or 0.0400% or less.
[0188] (La: 0~0.0500%)
[0189] La is an element that effectively controls the morphology of sulfides through trace addition, and should be added as needed. On the other hand, if La is present in excess, La inclusions are formed, which become the starting point for void formation and may therefore lead to a decrease in the bending resistance of the component during deformation. The La content can be 0% or more, or 0.0001% or more, or 0.0010% or more, or 0.0500% or less, or 0.0400% or less.
[0190] (Ce: 0~0.0500%)
[0191] Ce, like La, is an element whose sulfide morphology can be controlled by adding trace amounts, and it is added as needed. On the other hand, if Ce is present in excess, Ce inclusions are formed, which become the starting point for void formation, and may therefore lead to a decrease in the bending strength of the component during deformation. The Ce content can be 0% or more, or 0.0001% or more, or 0.0010% or more, or 0.0500% or less, or 0.0400% or less.
[0192] Regarding the steel plate in this embodiment, the remaining components described above are Fe and impurities. Impurities refer to components introduced during the industrial manufacturing of the steel plate of this embodiment through various factors in the manufacturing process, such as raw materials like ore and waste.
[0193] Next, the characteristics of the structure and properties of the steel plate according to the embodiments of the present invention will be described.
[0194] (Total area ratio of ferrite, pearlite and bainite: 0-30.0%)
[0195] While ferrite, pearlite, and bainite are effective microstructures for improving the balance between strength and ductility in steel sheets, their high content can lead to a decrease in localized ductility. Furthermore, from the viewpoint of effectively increasing steel strength, a lower area fraction of ferrite, pearlite, and bainite is preferred. The total area fraction of ferrite, pearlite, and bainite can be 0%, 1.0% or more, 30.0% or less, 25.0% or less, or 20.0% or less. It should be noted that although productivity may decrease slightly, by controlling continuous manufacturing conditions with high precision, the total area fraction of ferrite, pearlite, and bainite can be set to 0%.
[0196] (Area percentage of retained austenite: 10.0–30.0%)
[0197] Retained austenite is an effective microstructure for improving the strength-ductility balance of steel plates. If the area ratio of retained austenite is too small, the strength increase effect brought about by the process-induced phase transformation from retained austenite to martensite cannot be obtained when the steel plate is subjected to bending deformation, which may lead to a decrease in bending strength. On the other hand, if the area ratio of retained austenite is too large, it may lead to a decrease in yield strength and bending strength. The area ratio of retained austenite is 10.0% or more, or 13.0% or more, or 30.0% or less, or 25.0% or less.
[0198] In the steel sheet of this embodiment, the steel microstructure preferably contains acicular retained austenite. The following effects can be expected from the "acicular" morphology of the retained austenite: If the retained austenite is spherical (massive), processing-induced phase transformation is easily induced with deformation of the steel sheet, thus allowing bending deformation to begin at low stress. Conversely, if the retained austenite is acicular, processing-induced phase transformation becomes less likely, further increasing the bending strength. In the steel sheet of this embodiment, by combining the effects of the acicular retained austenite with the effects of the difference in the number and density of precipitates, the bending strength of the steel sheet is significantly improved. While setting the overall area ratio of retained austenite to 100%, the area ratio of acicular retained austenite can be 30% or more, or 50% or more, or 95% or less, or 90% or less. It should be noted that, in this application, "acicular retained austenite" refers to a retained austenite with a major-to-minor diameter ratio (major diameter / minor diameter) of 3.0 or greater. The "major diameter" and "minor diameter" of the retained austenite can be determined by microstructural observation using EBSD. Specifically, in microstructural observation, a retained austenite grain is identified, the smallest Freette diameter of that grain is determined as the minor diameter, and the largest Freette diameter is determined as the major diameter.
[0199] (Remaining portion: primary martensite and tempered martensite)
[0200] Primary martensite and tempered martensite are highly effective microstructures for increasing the strength of steel sheets, and a higher area ratio is preferred. In the steel sheet of this embodiment, the remaining portion other than ferrite, pearlite, bainite, and retained austenite is formed by primary martensite and tempered martensite. The total area ratio of primary martensite and tempered martensite can be 40.0% or more, 45.0% or more, 50.0% or more, or 90.0% or less, or 85.0% or less. Furthermore, the area ratio of primary martensite can be 5% or more, 10% or more, 20% or more, 30% or more, or 40% or more, or 80% or less, 70% or less, 60% or less, 50% or less, or 40% or less. Furthermore, the area ratio of tempered martensite can be 5% or more, 10% or more, 20% or more, 30% or more, or 40% or less, or less than 80%, 70% or less, 60% or less, 50% or less, or less than 40%.
[0201] (Difference in the number density of precipitates in tempered martensite on the first surface and the second back surface of the steel plate: 0–10.0%)
[0202] The number density of precipitates in the tempered martensite on both the first and second surfaces of the steel plate is a crucial factor in increasing resistance to bending deformation. Higher number densities on both surfaces result in increased bending strength. A high density on one surface leads to strain deviation during bending deformation, while a lower density on the other surface causes yielding, thus reducing bending strength. Therefore, a smaller difference between the number densities of precipitates in the tempered martensite on the first surface and the second surface is preferable. Specifically, a difference of 10.0% or less is important. This difference can also be less than 8.0%, 6.0%, 4.0%, or 2.0%. In other words, in this embodiment, the ratio A1 / A2 of the number density A1 of the precipitates on the first surface of the steel plate to the number density A2 of the precipitates on the second back surface of the steel plate is 0.90 to 1.10, or it can be 0.92 or more, 0.94 or more, 0.96 or more, or 0.98 or more, or it can be 1.08 or less, 1.06 or less, 1.04 or less, or 1.02 or less. It should be noted that setting the difference in number densities to 0% increases the manufacturing load and manufacturing costs in order to achieve precise control of the steel plate microstructure. In this regard, the difference in number densities can also be 0.1% or more. Furthermore, the main body of the precipitates is carbides produced by tempering martensite. Besides cementite, the carbides can also be iron-based carbides or alloy carbides formed by alloying elements such as Cr, Ti, and V replacing iron and combining with carbon. It should be noted that the specific value of the number density of precipitates in the tempered martensite on the first surface and the second back surface of the steel plate can also be, for example, 1 precipitate / μm. 2 Above, 5 / μm 2 More than 10 or 10 / μm 2 The above can also be 300 per μm. 2 Below, 100 / μm 2 Below or 30 / μm 2 the following.
[0203] It should be noted that, for the sake of convenience, the “face” and “back” of the steel plate are distinguished in this application, but there is no particular limitation on which side of the steel plate is the face and which side is the back.
[0204] (Yield strength YS)
[0205] To improve the lightweight nature of structures using steel as a raw material and its resistance to plastic deformation, a high yield strength of the steel raw material is preferred. On the other hand, if the yield strength is too high, the shape change caused by elastic deformation after plastic processing, known as springback, may become more pronounced. In this embodiment, the yield strength of the steel plate can be 600 MPa or more, or 650 MPa or more. There is no particular upper limit to the yield strength, but from the viewpoint of suppressing the aforementioned springback effect, it can also be 1100 MPa or less, or 1050 MPa or less.
[0206] (Tensile strength TS)
[0207] To improve the lightweight nature of structures using steel as a raw material and enhance their resistance to plastic deformation, steel raw materials with high work hardening capacity are preferred, exhibiting maximum strength. On the other hand, if the tensile strength is too high, it may become prone to fracture with low energy during plastic deformation, reducing formability. The tensile strength of the steel plate is not particularly limited, but it can be above 900 MPa, above 980 MPa, or below 2000 MPa or below 1800 MPa.
[0208] (Total elongation t-El)
[0209] When cold-forming steel sheets to manufacture structures, elongation becomes necessary for finishing complex shapes. If the total elongation is too low, the raw material may crack during cold forming. On the other hand, while a higher total elongation is preferred, excessively increasing the total elongation requires a large amount of retained austenite in the steel structure, which may reduce its resistance to bending deformation. The total elongation of the steel sheet is not particularly limited, but it can be 13% or more, 20% or more, or 35% or less.
[0210] (Porosity)
[0211] When cold-forming steel sheets to manufacture structures, both elongation and porosity are required to achieve complex shapes. Insufficient porosity can lead to cracking of the raw material during cold forming. Conversely, while higher porosity is generally preferred, excessively high porosity results in a large amount of retained austenite in the steel microstructure, potentially reducing its resistance to bending deformation. The porosity λ of the steel sheet is not particularly limited, but can be 20% or more, 25% or more, or even 90% or less, or 80% or less.
[0212] (Flexibility)
[0213] When cold-forming steel sheets to manufacture structures, flexibility becomes necessary for finishing complex shapes. If the VDA (velocity of deviation) bend angle is too small, the raw material may crack during cold forming. Higher flexibility is preferred. The VDA bend angle of the steel sheet is not particularly limited, but it can be 45° or higher, or even 50° or higher.
[0214] (plate thickness)
[0215] Plate thickness is a factor affecting the rigidity of the formed steel component; the greater the plate thickness, the higher the rigidity of the component. If the plate thickness is too small, it may lead to a decrease in rigidity and reduced press formability due to unavoidable non-ferrous inclusions present within the steel plate. On the other hand, if the plate thickness is too large, the press forming load increases, leading to die wear and reduced productivity. There is no particular limitation on the thickness of the steel plate, but it can be greater than 0.2 mm or less than 6.0 mm.
[0216] Next, the methods for observing and measuring the organizations specified above, as well as the methods for measuring and evaluating the characteristics specified above, will be described.
[0217] (Method for determining the total area ratio of ferrite, pearlite, and bainite)
[0218] Tissue observation was performed using a scanning electron microscope. Prior to observation, the samples were wet-polished with sandpaper and then polished with diamond abrasive grains having an average particle size of 1 μm to achieve a mirror finish. The tissue was then etched using a 3% nitric acid-ethanol solution. The magnification was set to 3000x, and 10 images were randomly taken at 1 / 4 thickness positions on the surface of the steel plate, covering a 30 μm × 40 μm field of view. The tissue ratio was determined using a point counting method. For each obtained tissue image, a grid of 100 points was established, spaced 3 μm vertically and 4 μm horizontally. Tissue below these grid points was identified, and the tissue ratio in the steel plate was calculated by averaging the 10 images. Ferrite consisted of massive grains and contained no iron-based carbides with a major diameter greater than 100 nm. Bainite is an aggregate of lath-shaped grains that either contains no iron-based carbides with a major diameter greater than 20 nm, or contains iron-based carbides with a major diameter greater than 20 nm belonging to a single variant, i.e., a group of iron-based carbides elongating in the same direction. Here, a group of iron-based carbides elongating in the same direction refers to a group of iron-based carbides whose elongation directions differ by less than 5°. For bainite, a bainite grain is counted as one bainite grain if it is enclosed by grain boundaries with an orientation difference of 15° or more. Pearlite is a microstructure containing cementite precipitated in rows. The area captured with bright contrast in a two-electron image is considered pearlite, and its area fraction is calculated.
[0219] (Methods for distinguishing between primary martensite and tempered martensite)
[0220] Primary and tempered martensite were observed using scanning and transmission electron microscopy, revealing structures containing Fe-based carbides (1 Fe-based carbide per μm). 2 The above-mentioned structures were identified as tempered martensite, and the structures containing virtually no Fe-based carbides (less than 1 Fe-based carbide per μm) were further analyzed. 2 The structure was identified as primary martensite. Regarding Fe-based carbides, various crystal structures of Fe-based carbides have been reported, but any type of Fe-based carbide may be present. Depending on the heat treatment conditions, multiple types of Fe-based carbides may exist. In this application, the total area ratio A1 of ferrite, pearlite, and bainite is determined by the above method, and the area ratio A2 of retained austenite is determined by the method described later. The remainder obtained by subtracting the sum of area ratios A1 and A2 from 100% is considered as the total area ratio of primary martensite and tempered martensite.
[0221] (Method for determining the area ratio of retained austenite)
[0222] The area fraction of retained austenite was determined by X-ray determination as follows. First, the portion from the surface of the steel plate to one-quarter of its thickness was removed by mechanical and chemical grinding. The chemically ground surface was then measured using MoKα rays as characteristic X-rays. Then, the area fraction of retained austenite at the center of the plate thickness was calculated using the following formula based on the integral intensity ratio of the diffraction peaks of the body-centered cubic (bcc) phase (200) and (211) and the face-centered cubic (fcc) phase (200), (220), and (311).
[0223] Sγ=(I200f+I220f+I311f) / (I200b+I211b)×100
[0224] (Sγ is the area fraction of the retained austenite in the center of the plate thickness, I200f, I220f and I311f represent the intensities of the (200), (220) and (311) diffraction peaks of the fcc phase, respectively, and I200b and I211b represent the intensities of the (200) and (211) diffraction peaks of the bcc phase, respectively.)
[0225] For X-ray diffraction, the steel plate is thinned to a specified thickness by mechanical grinding, followed by strain removal through chemical or electrolytic grinding. Simultaneously, the sample is adjusted according to the above method, with the appropriate surface serving as the measurement surface, within a thickness range of 1 / 8 to 3 / 8. Of course, the aforementioned limit on X-ray intensity is not limited to approximately 1 / 4 of the plate thickness; by satisfying this requirement across as much thickness as possible, material anisotropy is further reduced. However, by measuring within a range of 1 / 8 to 3 / 8 of the steel plate's surface, the overall material properties of the steel plate can be roughly represented. Therefore, 1 / 8 to 3 / 8 of the plate thickness is used as the measurement range.
[0226] It should be noted that the area ratio of acicular retained austenite in the retained austenite can be determined, for example, by EBSD.
[0227] (Method for determining the number density of precipitates in tempered martensite on the first surface and the second back surface of a steel plate)
[0228] The number density of precipitates in tempered martensite on the first surface and the second back surface of the steel plate is determined as follows: First, a sample is collected at a depth of 1 / 8 of the thickness in the thickness direction of the steel plate (referring to the surface or back of the base steel plate; for example, in the case of a surface-treated steel plate with a coating or other surface treatment layer, this refers to the surface or back of the base steel plate excluding the surface treatment layer). This sample is then prepared as a thin film or a replica of the sample. The sample is observed using a transmission electron microscope at 10,000x magnification, and images are captured in at least 30 fields of view. The number density of precipitates per unit area is measured in each image, and the arithmetic mean of the number densities across the 30 fields of view is set as the number density of precipitates on the first surface or the second back surface. It should be noted that the field of view observed using a transmission electron microscope at 10,000x magnification is a rectangular region with one side approximately 600 nm. The area of the 30 field measurements used to determine the number density of precipitates is approximately 10.8 μm. 2 Width.
[0229] (Methods for determining yield strength YP, tensile strength TS, and total elongation t-El)
[0230] The tensile test for determining yield strength, tensile strength and total elongation is conducted in accordance with JIS Z 2241:2011. JIS No. 5 test pieces are collected from the direction where the length of the test piece becomes parallel to the rolling right angle of the steel strip.
[0231] (Method for determining porosity)
[0232] Regarding hole expansion performance, a circular hole with a diameter of 10 mm was punched under the condition that the clearance was 12.5%. The hole was formed using a 60° conical punch with the fins positioned on the die side, and the hole expansion rate λ (%) was used for evaluation. Five hole expansion tests were conducted, and the average value was taken as the hole expansion rate.
[0233] (Method for determining flexibility)
[0234] Regarding bending performance, tests were conducted using 60mm wide test pieces according to the German Association of the Automotive Industry (VDA) standard 238-100. The VDA bending angle was evaluated by measuring the maximum bending angle α. Furthermore, bending resistance was evaluated by dividing the load at a bending angle of 5° by the plate thickness.
[0235] <Methods for manufacturing steel plates>
[0236] The steel plate manufacturing method of this embodiment is characterized by using a material having the above-described chemical composition and continuously managing hot rolling, cold rolling, and annealing. Specifically, the steel plate manufacturing method of this embodiment is characterized by including the following steps: hot rolling and coiling a steel billet (steel slab billet) having the same chemical composition as described above regarding the steel plate; pickling, cold rolling, and annealing the obtained hot-rolled plate; and performing aging treatment followed by further annealing. More specifically, the steel plate manufacturing method of this embodiment is characterized by including the following steps:
[0237] Hot-rolled plates are obtained by hot rolling steel slabs having the above-mentioned chemical composition.
[0238] The hot-rolled sheet is then coiled.
[0239] The hot-rolled plates were pickled.
[0240] The above-mentioned hot-rolled sheet is cold-rolled to obtain a cold-rolled sheet;
[0241] The above-mentioned cold-rolled sheet is subjected to the first annealing (Q annealing);
[0242] The cold-rolled sheet that has undergone the first annealing is then subjected to a second annealing (IA annealing); and
[0243] An aging process is performed between the first annealing and the second annealing.
[0244] The first annealing process described above involves heating the cold-rolled sheet to a temperature below 1000°C within the austenitic single-phase region and then cooling it to obtain a martensitic structure with an area fraction of 90.0% or more.
[0245] The second annealing process described above involves holding the cold-rolled sheet in a two-phase region of ferrite and austenite to obtain retained austenite.
[0246] The aforementioned aging treatment includes: aging treatment 1, which involves subjecting one side of the cold-rolled sheet to a tensile deformation with a bending radius of less than 2.0 m at a temperature of 0–40°C for at least 20 hours; and aging treatment 2, which involves subjecting the other side of the cold-rolled sheet to a tensile deformation with a bending radius of less than 2.0 m at a temperature of 0–40°C for at least 20 hours. Hereinafter, each step will be described in detail, focusing on the key aspects of this embodiment.
[0247] (Finishing temperature of hot rolling)
[0248] In this embodiment, a hot-rolled plate is obtained by hot rolling a steel slab obtained by a known method such as continuous casting. Here, the finishing temperature of the hot rolling is a factor that effectively controls the texture of the original austenite grain size. From the viewpoint that a well-developed austenite rolling texture leads to anisotropy in steel properties, the finishing temperature is preferably 650°C or higher. Furthermore, from the goal of suppressing the inhomogeneity of texture caused by abnormal austenite grain growth, the finishing temperature is preferably set to 950°C or lower.
[0249] (Roll-up temperature of the roll material)
[0250] The temperature at which hot-rolled steel sheets are coiled (the coiling temperature of hot-rolled coils) is a factor that controls the formation state of oxide scale in the hot-rolled steel sheets and affects their strength. A thinner oxide scale on the surface of the hot-rolled steel sheet is preferable; therefore, a lower coiling temperature is preferred. It should be noted that extremely low coiling temperatures require specialized equipment. Furthermore, if the coiling temperature is too high, as mentioned above, the oxide scale on the surface of the hot-rolled steel sheet becomes significantly thicker. Based on these considerations, the temperature at which hot-rolled steel sheets are coiled can be below 700°C, below 680°C, above 0°C, or above 20°C.
[0251] (Pickling of hot-rolled steel plates)
[0252] Pickling of hot-rolled steel plates is for the purpose of removing oxide scale, etc., and pickling can be carried out under known pickling conditions.
[0253] (Reduction rate in cold rolling)
[0254] In cold rolling, if the total reduction ratio is too large, the ductility of the base steel sheet is lost, increasing the risk of breakage during cold rolling. In this regard, the total reduction ratio in cold rolling is preferably 85% or less. On the other hand, to fully promote recrystallization in the annealing process, it is preferable to set the total reduction ratio to 20% or more, more preferably 30% or more. Annealing can also be performed at a temperature of 700°C or less to reduce the cold rolling load before cold rolling.
[0255] (Holding temperature during the first annealing)
[0256] In the first annealing (Q annealing), the cold-rolled sheet used as the base material is heated to a temperature between Ac3 and 1000°C (i.e., the austenitic single-phase region and below 1000°C). The reason for setting the maximum heating temperature above Ac3 is that by heating the base material to the austenitic single-phase region, a martensite structure with a surface area of over 90% is obtained through subsequent quenching, promoting the precipitation of ε-carbides due to aging. A martensite-dominated structure cannot be obtained during holding at lower temperatures, resulting in a significant reduction in bending strength. On the other hand, if heated to above 1000°C, decarburization occurs on the surface of the steel sheet, leading to a decrease in strength and potentially a reduction in bending strength.
[0257] (Holding time during the first annealing)
[0258] In the first annealing (Q annealing), it is preferable to hold the heat at a temperature of Ac3 to 1000°C for at least 5 seconds. This is because if the holding time is too short, the austenitic transformation of the base steel sheet becomes insufficient, and the concentration of substitutional elements such as Mn, which stabilize austenite, in the austenite becomes insufficient. Therefore, the residual austenite may become unstable, and the ductility of the steel sheet may decrease significantly. From these viewpoints, a holding time of 10 seconds or more is more preferable. More preferably, 20 seconds or more is preferred.
[0259] (Atmosphere during the first annealing)
[0260] In the first annealing (Q annealing), to improve the flexibility of the steel sheet by imparting a decarburized layer to the surface, the oxygen potential in one or both of the heating zone and the soaking zone during annealing can be controlled. Specifically, annealing is preferably carried out in an atmosphere containing 0.1 to 30 vol% hydrogen and H2O with a dew point of -40 to 20°C, with the remainder being nitrogen and impurities. More preferably, an atmosphere containing 0.5 to 20 vol% hydrogen and H2O with a dew point of -30 to 15°C is used, and even more preferably, an atmosphere containing 1 to 10 vol% hydrogen and H2O with a dew point of -20 to 10°C is used.
[0261] (Cooling rate during the first annealing)
[0262] In the first annealing (Q annealing), it is preferable to cool from 750°C to 550°C at an average cooling rate of 100°C / second or less during cooling after heating and holding. The lower limit of the average cooling rate is not particularly limited, as long as a martensitic structure with an area fraction of 90% or more is obtained; for example, it can be 3°C / second. The reason for setting the lower limit of the average cooling rate to 3°C / second is to suppress the formation of ferrite phase transformation in the base steel sheet, so that the martensite area fraction in the steel structure after Q annealing becomes less than 90%. More preferably, it is 10°C / second or more, even more preferably 15°C / second or more, and even more preferably 20°C / second or more. On the other hand, if the cooling rate from 750°C to 550°C is too fast, a low-temperature phase transformation structure also forms in the surface layer of the steel sheet, resulting in uneven hardness. In this regard, the average cooling rate is preferably 100°C / second or less, more preferably 80°C / second or less, and even more preferably 50°C / second or less. It should be noted that ferrite phase transformation is significantly difficult to occur above 750℃, therefore the cooling rate is not limited. Furthermore, low-temperature phase transformation structures can be obtained at temperatures below 550℃, therefore the cooling rate is not limited.
[0263] (Cooling stop temperature and reheating during the first annealing)
[0264] Furthermore, after the aforementioned cooling, the temperature can be further cooled to 25°C to 550°C, followed by a residence time within the temperature range of 150°C to 550°C. The lower limit of the cooling stop temperature is set at 25°C because excessive cooling not only requires significant equipment investment but also saturates its effect. The residence time is not particularly limited, but can be, for example, 30 to 500 seconds.
[0265] (Time-sensitive processing 1)
[0266] Maintaining the steel sheet with a bending radius R of 2.0 m or less under a bending deformation condition at 0–40 °C for more than 20 hours, after the first annealing has controlled the microstructure to be predominantly martensite, is an important factor for increasing the bending strength of the steel sheet. During this treatment, carbon atoms dissolved in the martensite form clusters or transition carbides, which become nuclei for carbide precipitation during the subsequent second annealing. To improve bending strength by finely dispersing the carbides, it is important that the clusters or transition carbides that serve as carbide precipitates are fine and exist at a high density. Effective utilization of tensile strain is extremely effective in promoting the formation of clusters or transition carbides, and this effect is easily obtained in bending deformation with a bending radius R of 2.0 m or less. The bending radius R can also be 1.8 m or less, 1.5 m or less, or 1.3 m or less. On the other hand, if the bending radius R exceeds 2.0 m, it becomes difficult to obtain this effect. For example, by rolling up the steel sheet (steel strip) after the first annealing to form a coil, the steel sheet can be subjected to the aforementioned bending deformation.
[0267] Furthermore, maintaining a temperature below 0°C inhibits the clustering of carbon atoms or the formation of transition carbides. Maintaining a temperature above 40°C leads to coarser formation of transition carbides (reduced nuclei), making it difficult to obtain fine carbides during the second annealing process, thus reducing flexural strength. If the holding temperature in aging treatment 1 and aging treatment 2 (described later) is within the range of 0–40°C, the difference in the number of precipitates between aging treatment 1 and aging treatment 2 becomes smaller, and the difference in precipitate density between the first surface of the steel plate and the second back surface of the steel plate becomes less than 10%. The holding temperature can also be above 5°C, above 10°C, below 35°C, or below 30°C.
[0268] Furthermore, when the holding time is less than 20 hours, the number of nuclei generated may be unstable, and a sufficient amount of nuclei may not be generated, making it difficult to suppress the difference between the number density of precipitates on the first surface of the steel plate and the number density of precipitates on the second back surface of the steel plate to within 10%. A longer holding time is preferable, which can be 30 hours or more, 40 hours or more, or 50 hours or more. Furthermore, if the holding time exceeds 300 hours, the clustering of carbon atoms or the formation of transition carbides becomes saturated, and the morphology (size) of the precipitates becomes less likely to change significantly during longer holding times; therefore, a holding time of 300 hours or less is also acceptable. It should be noted that if the holding time becomes very long, although the precipitates become larger, the number of precipitates does not change significantly. That is, if the holding time of aging treatment 1 and aging treatment 2 described below is more than 20 hours, the number of generated nuclei is stable, and the difference between the number density of precipitates on the first surface of the steel plate and the number density of precipitates on the second back surface of the steel plate is within 10%.
[0269] (Time-sensitive processing 2)
[0270] When bending deformation is applied to the steel sheet to promote aging, the clustering of carbon atoms and the precipitation of transition carbides are significantly caused in the area subjected to tensile deformation. Therefore, when only one winding and unwinding process is performed through the aforementioned aging treatment 1, the precipitates are finely dispersed only on one side of the steel sheet. Therefore, in the manufacturing method of this embodiment, after aging treatment 1, in which the precipitates are precipitated and dispersed on one side of the steel sheet (surface and back), aging treatment 2, in which the precipitates are precipitated and dispersed on the other side of the steel sheet (surface and back), is performed. For example, after the first annealing, the steel sheet is rolled into a coil with the outer side facing outwards and the back side facing inwards. After aging treatment 1, the outer side of the steel sheet is subjected to tensile deformation with a bending radius R of 2.0 m or less. Then, the coil is unwound, and the steel sheet is rolled into a coil again with the back side facing outwards and the outer side facing inwards. Aging treatment 2 is then performed on the back side of the steel sheet with tensile deformation of a bending radius R of 2.0 m or less. In aging treatment 2, the bending deformation with a bending radius R of 2.0 m or less is performed under the same conditions as in aging treatment 1, thereby suppressing the difference between the number density of precipitates on the first surface of the steel sheet and the number density of precipitates on the second back side of the steel sheet to within 10%. The bending radius R can also be 1.8 m or less, 1.5 m or less, or 1.3 m or less. On the other hand, if the bending radius R exceeds 2m, it becomes difficult to suppress the difference in the number density of precipitates to within 10%.
[0271] Furthermore, in aging treatment 2, similarly to aging treatment 1, maintaining the temperature below 0°C inhibits the clustering of carbon atoms or the formation of transition carbides. Maintaining the temperature above 40°C leads to coarser formation of transition carbides (reduced number of nuclei), making it difficult to obtain fine carbides during the second annealing, thus reducing flexural strength. As described above, if the holding temperature in aging treatment 1 and aging treatment 2 (described later) is within the range of 0 to 40°C, the difference between the number density of precipitates on the first surface of the steel plate and the number density of precipitates on the second back surface of the steel plate is within 10%. The holding temperature can also be 5°C or higher, 10°C or higher, 35°C or lower, or 30°C or lower.
[0272] Furthermore, in aging treatment 2, similarly to aging treatment 1, if the holding time is less than 20 hours, the number of nuclei generated may be unstable, making it difficult to suppress the difference between the number density of precipitates on the surface (first side) of the steel plate and the number density of precipitates on the back (second side) of the steel plate to within 10%. A longer holding time is preferable, such as 30 hours or more, 40 hours or more, or 50 hours or more. It should be noted that, similar to aging treatment 1, if the holding time exceeds 300 hours, the clustering of carbon atoms or the formation of transition carbides becomes saturated, and the morphology (size) of the precipitates becomes less likely to change significantly during longer holding periods. Therefore, a holding time of 300 hours or less is also acceptable.
[0273] (Holding temperature during the second annealing)
[0274] The holding temperature in the second annealing (IA annealing) is the temperature at which the dual-phase region of ferrite and austenite is formed. For example, it is preferably 720°C to 860°C. If the annealing temperature is below 720°C, austenite will not be sufficiently generated. In this case, since the martensite obtained in the first annealing (Q annealing) is tempered, carbides precipitate, and the required area ratio of retained austenite may not be met. Furthermore, since the area ratio of austenite at the highest heating temperature (annealing temperature) also decreases, it may be impossible to concentrate the carbon required to obtain retained austenite in the austenite, making it impossible to ensure a retained austenite content of 10.0% or more. On the other hand, if the annealing temperature exceeds 860°C, excessive austenite may be generated, resulting in a decrease in flexural strength due to the reduction of tempered martensite containing precipitates, and it may also be impossible to ensure a retained austenite content of 10.0% or more. Therefore, the upper limit of the holding temperature in the second annealing is preferably set to 860°C. Annealing can be carried out in the atmosphere or, to improve the adhesion of the coating, in an atmosphere where hydrogen concentration and dew point are controlled.
[0275] (Holding time during the second annealing)
[0276] In the second annealing (IA annealing), it is preferable to hold the steel at a heating temperature of 720°C to 860°C for at least 5 seconds. If the holding time is too short, the austenitic transformation of the base steel sheet becomes insufficient, and the concentration of substitutional elements such as Mn that stabilize austenite in the austenite becomes insufficient. Therefore, the residual austenite may become unstable, and the ductility of the steel sheet may decrease significantly. From these points of view, a holding time of 10 seconds or more is more preferable. More preferably, it is 20 seconds or more.
[0277] (Atmosphere during the second annealing)
[0278] In the second annealing (IA annealing), similarly to the first annealing (Q annealing), in order to impart a decarburized layer to the surface of the steel sheet to improve its flexibility, the oxygen potential in one or both of the heating zone and the soaking zone during annealing can be controlled. Specifically, annealing is preferably carried out in an atmosphere containing 0.1 to 30 vol% hydrogen and H2O with a dew point of -40 to 20°C, with the remainder being nitrogen and impurities. More preferably, an atmosphere containing 0.5 to 20 vol% hydrogen and H2O with a dew point of -30 to 15°C is used, and even more preferably, an atmosphere containing 1 to 10 vol% hydrogen and H2O with a dew point of -20 to 10°C is used.
[0279] (Cooling rate during the second annealing)
[0280] In the second annealing (IA annealing), it is preferable to cool from 750°C to 550°C at an average cooling rate of 100°C / second or less during the cooling process after heating and holding. The lower limit of the average cooling rate is not particularly limited, but can be, for example, 2.5°C / second. The reason for setting the lower limit of the average cooling rate to 2.5°C / second is to suppress the ferrite phase transformation caused by the concentration of alloying elements in the acicular austenite in the base steel sheet, thereby preventing softening of the base steel sheet. If the average cooling rate is too slow, the strength is prone to decrease. More preferably, it is 5°C / second or more, further preferably 10°C / second or more, and even more preferably 20°C / second or more. On the other hand, if the cooling rate from 750°C to 550°C is too fast, a low-temperature phase transformation structure is also generated in the surface layer of the steel sheet, resulting in uneven hardness. In this regard, the average cooling rate is preferably 100°C / second or less, more preferably 80°C / second or less, and even more preferably 50°C / second or less. It should be noted that ferrite phase transformation is significantly difficult to occur above 750℃, therefore the cooling rate is not limited. Furthermore, low-temperature phase transformation structures can be obtained at temperatures below 550℃, therefore the cooling rate is not limited.
[0281] (Cooling stop temperature and reheating during the second annealing)
[0282] Furthermore, after the aforementioned cooling, the temperature can be further cooled to 25°C to 550°C, followed by reheating to a temperature range of 150°C to 550°C for residence. If cooling is performed within this temperature range, martensite is formed from untransformed austenite during cooling. Subsequently, reheating causes carbon to concentrate from the martensite into the untransformed austenite, improving the strength-ductility balance of the steel sheet. The lower limit of the cooling stop temperature is set at 25°C because excessive cooling not only requires significant equipment investment but also saturates its effect. The residence time is not particularly limited, but can be, for example, 30 seconds to 500 seconds.
[0283] (Conditions for obtaining needle-like retained austenite in the second annealing)
[0284] In the steel sheet manufacturing method of this embodiment, it is preferable to obtain acicular retained austenite in the second annealing (IA annealing). For example, by making the area ratio of the retained austenite obtained by IA annealing 10 to 50%, and by controlling the temperature in the holding process of IA annealing such that the temperature change of the steel sheet is within ±3°C per second, the alloying elements segregate at the interface between ferrite and austenite held in the dual-phase region, thereby reducing the migration of the interface. Thus, acicular retained austenite can be obtained even at room temperature.
[0285] (Retention temperature)
[0286] Furthermore, the steel sheet can be held in a temperature range of 350–550°C after reheating and before immersion in the plating bath. This holding in this temperature range not only aids in the tempering of martensite but also eliminates temperature unevenness in the width direction of the steel sheet, improving the appearance after plating. It should be noted that if the cooling stop temperature is 350°C–550°C, holding without reheating is sufficient.
[0287] (Duration of stay)
[0288] To achieve the desired effect, the dwell time is preferably set to 30 to 300 seconds.
[0289] (Tempering)
[0290] In a series of annealing processes, cold-rolled steel sheets or coated steel sheets that have undergone plating treatment can be cooled to room temperature or, during the cooling process (below Ms), reheated and held at a temperature range of 150°C to 400°C for at least 2 seconds. According to this process, tempered martensite is produced by tempering the martensite generated during the cooling after reheating, which improves resistance to hydrogen embrittlement. In the tempering process, if the holding temperature is too low or the holding time is too short, the martensite will not be sufficiently tempered, and the microstructure and mechanical properties will remain almost unchanged. On the other hand, if the holding temperature is too high, the dislocation density in the tempered martensite decreases, leading to a decrease in tensile strength. Therefore, in the tempering process, it is preferable to hold at a temperature range of 150°C to 400°C for at least 2 seconds. Tempering can be performed in a continuous annealing apparatus or offline using other equipment after continuous annealing. In this case, the tempering time varies depending on the tempering temperature. That is, the lower the temperature, the longer the duration; the higher the temperature, the shorter the duration.
[0291] (plating)
[0292] Alternatively, the steel sheet can be heated or cooled to (galvanizing bath temperature -40)°C to (galvanizing bath temperature +50)°C as needed to perform hot-dip galvanizing. Through the hot-dip galvanizing process, a hot-dip galvanized layer is formed on the surface of the steel sheet. In this case, the corrosion resistance of the cold-rolled sheet is improved, and therefore it is preferred. In this embodiment, the type of coating is not limited to a hot-dip galvanized layer, and various coatings can be used. Furthermore, there is no particular limitation on the timing of coating the surface of the steel sheet. For example, in the manufacturing method of this embodiment, a coating layer containing zinc, aluminum, magnesium, or alloys thereof can be formed on the front and back surfaces of the steel sheet during 1A annealing, after holding the cold-rolled sheet in the ferrite-austenite dual-phase region and cooling it to room temperature. Alternatively, this coating layer can be formed on the front and back surfaces of the annealed steel sheet.
[0293] (Temperature of the steel plate during immersion in the plating bath)
[0294] The preferred temperature range for immersion in the hot-dip galvanizing bath is between 40°C lower than the bath temperature (hot-dip galvanizing bath temperature -40°C) and 50°C higher (hot-dip galvanizing bath temperature +50°C). If this temperature is lower than the bath temperature -40°C, excessive heat dissipation during immersion may cause some of the molten zinc to solidify, resulting in a deterioration of the coating appearance. If the plate temperature before immersion is lower than the bath temperature -40°C, it can be further heated by any method before immersion to control the steel plate temperature above the bath temperature before immersion. Furthermore, if the steel plate temperature during immersion exceeds the bath temperature +50°C, operational problems may arise due to the increased bath temperature.
[0295] (Composition of the plating bath)
[0296] The plating bath is preferably composed mainly of Zn, with an effective Al content (the value obtained by subtracting the total Fe content from the total Al content in the plating bath) of 0.050 to 0.250% by mass. If the effective Al content in the plating bath is too low, Fe may excessively penetrate into the coating, reducing the coating adhesion. On the other hand, if the effective Al content in the plating bath is too high, Al-based oxides that hinder the movement of Fe and Zn atoms may form at the boundary between the steel plate and the coating, reducing the coating adhesion. The effective Al content in the plating bath is more preferably 0.065% by mass or more, and more preferably 0.180% by mass or less.
[0297] (Temperature of the steel plate after immersion in the plating bath)
[0298] When alloying a hot-dip galvanized layer, the steel sheet with the hot-dip galvanized layer is heated to a temperature range of 450–600°C. If the alloying temperature is too low, alloying may not proceed sufficiently. On the other hand, if the alloying temperature is too high, over-alloying may occur, resulting in the formation of the Γ phase and causing the Fe concentration in the coating to exceed 15%, thereby deteriorating corrosion resistance. An alloying temperature of 470°C or higher is more preferably, and 550°C or lower is even more preferably. Since the alloying temperature needs to be adjusted according to the composition of the steel sheet, it can be set while simultaneously checking the Fe concentration in the coating.
[0299] (Preprocessing)
[0300] To further improve the adhesion of the coating, the steel sheet can be coated with one or more of Ni, Cu, Co and Fe before annealing in a continuous hot-dip galvanizing production line.
[0301] (Post-processing)
[0302] For the purpose of improving paintability and weldability, an upper coating or various treatments such as chromate treatment, phosphate treatment, lubricity improvement treatment, and weldability improvement treatment may be applied to the coating surface of hot-dip galvanized steel sheet having a steel plate and a hot-dip galvanized layer formed on the surface of the steel plate, or to the coating surface of alloyed hot-dip galvanized steel sheet having a steel plate and an alloyed hot-dip galvanized layer formed on the surface of the steel plate.
[0303] (Surface smoothing ratio)
[0304] Furthermore, skin rolling can also be implemented with the aim of improving ductility through correction of the steel plate shape or introduction of movable dislocations. The reduction rate of skin rolling after heat treatment is preferably in the range of 0.1% to 1.5%. A reduction rate below 0.1% has little effect and is difficult to control, thus it is set as the lower limit. If the reduction rate exceeds 1.5%, productivity decreases significantly, therefore it is set as the upper limit. Skin rolling can be performed online or offline.
[0305] <Supplement>
[0306] It should be noted that the difference in hardness between the surface and back of the steel sheet is not substantially related to the difference in the number density of precipitates on the surface and back of the steel sheet. That is, even if the difference in hardness between the surface and back of the steel sheet is reduced, the difference in the number density of precipitates on the surface and back of the steel sheet cannot be reduced, and the bending strength of the steel sheet may not necessarily be improved, nor can the difference in bending strength between the surface and back of the steel sheet be reduced. As with the steel sheet of this embodiment, by reducing the difference in the number density of precipitates on the surface and back of the steel sheet, the bending strength of the steel sheet can be improved, and the difference in bending strength between the surface and back of the steel sheet can be reduced. In order to reduce the difference in the number density of precipitates on the surface and back of the steel sheet, as in the manufacturing method of the steel sheet of this embodiment, it is effective to perform aging treatments 1 and 2 between the first annealing (Q annealing) and the second annealing (IA annealing) of the cold-rolled sheet. Previously, no research had been conducted on reducing the difference in the number and density of precipitates on the surface and back of the steel plate, and no plans had been made for Q annealing, aging treatments 1 and 2, and IA annealing as in the manufacturing method of this embodiment.
[0307] Example
[0308] The following illustrates an embodiment of the present invention. The present invention is not limited to this single example. Various conditions may be employed to achieve the present invention without departing from its spirit and purpose.
[0309] (Example 1)
[0310] Steel billets are manufactured by melting steels with various chemical compositions. These billets are then inserted into a furnace heated to 1220°C, held for 60 minutes for homogenization, and then exposed to atmosphere for hot rolling to obtain a steel sheet with a thickness of 2.8 mm. In the hot rolling process, the finishing temperature is 910°C, and the sheet is cooled to 550°C for coiling. Next, the oxide scale on the hot-rolled sheet is removed by pickling, followed by cold rolling with a reduction rate of 45.0% to finish the sheet thickness to 1.54 mm. The cold-rolled sheet is then Q-annealed, specifically heated to 930°C and held for 90 seconds within this temperature range. The cold-rolled sheet is then cooled and held at 280°C, and coiled into a coil shape with a maximum radius of 1.4 m. The martensite area ratio in the coiled steel sheet is over 90% in any steel composition. A aging treatment 1, in which the coiled material is held at a temperature range of 6°C to 22°C for 38 hours, is performed. Then, the coil is unwound and wound again to form a coil with a maximum radius of 1.4 m. While bending the steel sheet in the opposite direction to aging treatment 1, another aging treatment 2, held at a temperature range of 6°C to 22°C for 38 hours, is performed. Next, the aging-treated steel sheet is subjected to IA annealing, specifically heated to 785°C, with a holding time of 130 seconds within this temperature range. Then, the aging-treated steel sheet is cooled to 270°C, then heated to 390°C and held at this temperature for 140 seconds. After cooling to room temperature, surface finishing is performed. The chemical composition of samples collected from each of the resulting steel sheets is shown in Tables 1-3. It should be noted that in Tables 1-3, "-" indicates values below the detection limit. The components other than those shown in Tables 1-3 are Fe and impurities. Furthermore, Table 4 presents the evaluation results of the properties of the steel sheet after the aforementioned processing and heat treatment.
[0311] Furthermore, in Table 4, the methods for determining the "area ratio," "yield strength YS," "tensile strength TS," "total elongation t-El," "pore expansion ratio λ," and "difference in the number density of precipitates in tempered martensite" for each microstructure and phase in the steel microstructure are as described above. Regarding "yield strength YS," a value of 600 MPa or higher is considered "qualified." Furthermore, regarding "bending resistance (flexural strength)," both (1) the bending resistance value of the steel plate itself and (2) the difference in bending resistance between the front and back surfaces of the steel plate are used as evaluation indicators. Specifically, the value of (1) "bending resistance" is determined based on the load during VDA bending as described above. Specifically, bending tests are performed on both sides of the steel plate. A load of 1400N or more per 1mm of plate thickness on both sides at a 5° bending angle is classified as "A"; a load of 900N or more but less than 1400N is classified as "B"; a load less than 900N is classified as "C"; and a result of A or B is classified as "qualified". Furthermore, regarding (2) "poor bending resistance of the steel plate's front and back sides," the judgment is also based on the load during VDA bending. Specifically, a load difference of less than 3% between the front and back sides when subjected to a specified bend is classified as "A"; a difference exceeding 3% but less than 8% is classified as "B"; a difference exceeding 8% is classified as "C"; and a result of A or B is classified as "qualified".
[0312]
[0313]
[0314]
[0315]
[0316]
[0317]
[0318]
[0319]
[0320]
[0321] The following information can be obtained from the results shown in Tables 1-4.
[0322] Because the carbon content in BA-1 steel plate is too low, the yield strength YS and tensile strength TS of the steel are reduced, and sufficient bending resistance (bending capacity) cannot be guaranteed.
[0323] BB-1 steel has a high carbon content, which reduces its elongation and leads to brittle fracture, thus reducing its bending resistance.
[0324] It is believed that the low Si content in BC-1 steel reduces the stability of the retained austenite structure during processing, making it unable to suppress the precipitation of carbides in the martensite structure during aging. As a result, the combined area fraction of ferrite, pearlite, and bainite increases, leading to a decrease in the yield strength (YS) and tensile strength (TS) of the steel plate. Furthermore, the reduced area fraction of retained austenite prevents the strength increase resulting from the processing-induced phase transformation from retained austenite to martensite when the steel plate is subjected to bending deformation, and also fails to ensure sufficient bending resistance.
[0325] It is believed that the excessive Si content in BD-1 steel inhibits the formation of ε-carbides during aging treatment. As a result, adequate bending resistance cannot be guaranteed.
[0326] Because of its low Mn content, BE-1 steel is prone to ferritic phase transformation during Q-annealing. This results in a lower martensite ratio after Q-annealing, ultimately reducing the area ratio of retained austenite in the final steel sheet. Consequently, the yield strength (YS) and tensile strength (TS) of the steel sheet decrease. Furthermore, the strength increase induced by the process-induced phase transformation from retained austenite to martensite cannot be achieved when the steel sheet is subjected to bending deformation, and sufficient bending resistance cannot be guaranteed.
[0327] It is believed that the excessive Mn content in BF-1 steel plate leads to a significant Mn-concentrated layer formed by micro-segregation and central segregation. This is caused by the difference in solidification rate between the front and back surfaces of the slab, resulting in a difference in the distribution of the Mn-concentrated layer. Consequently, the difference in the formation of Mn segregation bands leads to differences in the number and density of precipitates in the tempered martensite, resulting in differences in the bending resistance between the front and back surfaces. As a result, sufficient bending resistance cannot be guaranteed.
[0328] It is believed that the excessive phosphorus (P) content in BG-1 steel plates leads to brittle fracture, which in turn reduces the bending resistance during bending deformation. As a result, adequate bending resistance cannot be guaranteed.
[0329] It is believed that the excessive sulfur content in BH-1 steel plates leads to the formation of non-metallic inclusions, resulting in reduced ductility and the creation of voids originating from these inclusions during bending deformation. Consequently, adequate bending resistance cannot be guaranteed.
[0330] It is believed that due to the excessive Al content in BI-1 steel plates, the ferrite and bainite phase transformations during the cooling process in annealing are excessively promoted. As a result, the yield strength YS and tensile strength TS of the steel plates are reduced, and sufficient bending resistance cannot be guaranteed.
[0331] It is believed that BJ-1 steel has an excessive nitrogen content, which combines with al to form a large amount of AlN. These nitrides become the starting point for voids to form during bending deformation. As a result, sufficient bending resistance cannot be guaranteed.
[0332] It is believed that BK-1 steel has an excessive Ti content, resulting in more coarse carbide precipitation. These carbides become the starting point for voids during bending deformation. As a result, sufficient bending resistance cannot be guaranteed.
[0333] It is believed that BL-1 steel has an excessive Co content, resulting in the precipitation of numerous fine Co carbides. These carbides become the starting point for voids to form during bending deformation. Consequently, adequate bending resistance cannot be guaranteed.
[0334] It is believed that the excessive Ni content in BM-1 steel affects the peeling properties of oxide scale during hot rolling, promoting the formation of scratches on the steel surface. As a result, adequate bending resistance cannot be guaranteed.
[0335] It is believed that BN-1 steel, due to its excessive Mo content, produces a large amount of fine Mo carbides, which become the starting point for voids during bending deformation. As a result, adequate bending resistance cannot be guaranteed.
[0336] BO-1 steel has an excessive Cr content, which promotes the formation of retained austenite. Due to the presence of excessive retained austenite, it cannot ensure sufficient bending resistance.
[0337] It is believed that BP-1 steel has an excessive oxygen content, resulting in the formation of a large amount of oxides as inclusions. These oxides, present on the punched and cut surfaces, cause notch-like scratches and large dimples on the end faces. During bending deformation, this leads to stress concentration, becoming the starting point for crack formation. Consequently, adequate bending resistance cannot be guaranteed.
[0338] It is believed that BQ-1 steel, due to its excessive boron (B) content, attracts large B inclusions, which become the starting point for voids. As a result, adequate bending resistance cannot be guaranteed.
[0339] It is believed that BR-1 steel has an excessive Nb content, resulting in the precipitation of a large amount of fine and hard Nb carbides, which become the starting point for void formation. As a result, adequate bending resistance cannot be guaranteed.
[0340] It is believed that BS-1 steel has an excessive V content, resulting in increased carbonitride precipitation, which becomes the starting point for void formation. Consequently, adequate bending resistance cannot be guaranteed.
[0341] It is believed that BT-1 steel, due to its excessive Cu content, exhibits reduced ductility despite increased strength. Consequently, its bending resistance during bending deformation is reduced, failing to ensure adequate bending resistance.
[0342] It is believed that BU-1 steel, due to its excessive W content, facilitates the development of voids starting with coarse carbides. As a result, adequate bending resistance cannot be guaranteed.
[0343] It is believed that BV-1 steel, due to its excessive Ta content, produces a large amount of fine Ta carbides, which facilitate the formation of voids. As a result, adequate bending resistance cannot be guaranteed.
[0344] It is believed that BW-1 steel has too much Sn content, which reduces its bending resistance during bending deformation due to the embrittlement of the steel plate, thus failing to ensure sufficient bending resistance.
[0345] It is believed that BX-1 has excessive Sb content in its steel plate, which reduces its bending resistance during bending deformation due to the embrittlement of the steel plate, thus failing to ensure sufficient bending resistance.
[0346] It is believed that BY-1 has excessive As content in its steel plate, which reduces its bending resistance during bending deformation due to the embrittlement of the steel plate, thus failing to ensure sufficient bending resistance.
[0347] It is believed that the excessive Mg content in the BZ-1 steel plate leads to the formation of large inclusions, which become the starting point for voids. As a result, adequate bending resistance cannot be guaranteed.
[0348] It is believed that CA-1 steel has too much Ca content, which reduces its bending resistance during bending deformation due to the embrittlement of the steel plate, thus failing to ensure sufficient bending resistance.
[0349] It is believed that CB-1 steel has an excessive amount of γ (yellow) in its sheet, resulting in the formation of large γ inclusions, which become the starting point for void formation. As a result, adequate bending resistance cannot be guaranteed.
[0350] It is believed that CC-1 steel has an excessive Zr content, resulting in the formation of large Zr inclusions, which become the starting point for void formation. As a result, adequate bending resistance cannot be guaranteed.
[0351] It is believed that CD-1 steel has an excessive La content, resulting in the formation of La inclusions, which become the starting point for void formation. As a result, adequate bending resistance cannot be guaranteed.
[0352] It is believed that CE-1 steel has an excessive Ce content, which leads to the formation of Ce inclusions, and these inclusions become the starting point for voids. As a result, adequate bending resistance cannot be guaranteed.
[0353] In contrast, regarding A-1 to AZ-1, by manufacturing steel sheets with a specified chemical composition under specified conditions, a specified metallic structure is obtained in the steel sheets, and the mechanical properties and bending resistance of the steel sheets are excellent. Furthermore, regarding the steel sheets containing tempered martensite obtained in Example 1, the precipitate number density is 1 precipitate / μm. 2 ~300 cells / μm 2 Within the range.
[0354] (Example 2)
[0355] Furthermore, to investigate the influence of manufacturing conditions, steel grades A to AZ, which were identified as having excellent properties in Table 1, were used as subjects. Hot-rolled sheets with a thickness of 2.8 mm were produced at the finishing rolling temperatures listed in Tables 5 to 7. These hot-rolled sheets were then coiled, pickled, and cold-rolled to produce cold-rolled sheets. The cold-rolled sheets were then annealed and aged, and optionally coated to obtain steel sheets for property evaluation. Here, the coated steel sheets were immersed in a hot-dip galvanizing bath and held at the temperatures shown in Tables 5 to 7 to produce alloyed hot-dip galvanized steel sheets with an iron-zinc alloy coating on the surface. In addition, for some steel sheets, before cooling to room temperature after being held at various holding temperatures during the annealing of the cold-rolled sheets, a tempering treatment was performed: the steel sheets temporarily cooled to 150°C were reheated to a specified temperature and held for at least 2 seconds. The results are shown in Tables 5 to 7. It should be noted that the method for evaluating the properties is the same as in Example 1.
[0356] (Table 5-1)
[0357]
[0358] (Table 5-2)
[0359]
[0360]
[0361] (Table 6-1)
[0362]
[0363] (Table 6-2)
[0364]
[0365]
[0366] (Table 7-1)
[0367]
[0368] (Table 7-2)
[0369]
[0370]
[0371] The following information can be obtained from the results shown in Tables 5-7.
[0372] Regarding A-2 and X-2, because the aging time in aging treatment 1 is too short, the difference in the amount of precipitates precipitated in aging treatment 1 and aging treatment 2 becomes larger. As a result, the difference in the number density of precipitates in the tempered martensite on the surface and back of the steel plate becomes larger, and the bending resistance of the steel plate decreases.
[0373] Regarding C-2 and S-3, it is believed that decarburization occurs on the surface of the steel sheet due to excessively high annealing temperatures during Q annealing. As a result, the strength of the steel sheet is reduced, and sufficient bending resistance cannot be guaranteed.
[0374] Regarding I-2 and W-2, due to the excessively high annealing holding temperature in IA annealing (since the annealing holding temperature is outside the range of the ferrite-austenite duplex region), excessive austenite is formed, resulting in a decrease in flexural strength due to the reduction of tempered martensite containing precipitates. Furthermore, the elongation is also reduced because it is impossible to ensure a residual austenite content of more than 10.0%.
[0375] Regarding L-2 and Z-3, the annealing holding temperature in IA annealing is too low (since the annealing holding temperature is outside the range of the ferrite-austenite dual-phase region), therefore, austenite is not sufficiently formed, and the martensite obtained in Q annealing is tempered, thus failing to ensure a retained austenite content of more than 10.0%. As a result, the strength increase effect brought about by the process-induced phase transformation from retained austenite to martensite cannot be obtained when bending deformation is applied to the steel sheet, and sufficient bending resistance cannot be ensured.
[0376] Regarding E-3 and AX-2, due to the low annealing holding temperature in Q annealing, the base steel sheet cannot be heated to the austenitic single-phase region, thus reducing the martensite area ratio after Q annealing. As a result, a sufficient amount of ε-carbides cannot precipitate during aging treatment, failing to ensure adequate bending resistance. Furthermore, the reduced area ratio of retained austenite means that the strength increase effect brought about by the process-induced phase transformation from retained austenite to martensite cannot be obtained when bending deformation is applied to the steel sheet; from this perspective, adequate bending resistance also cannot be guaranteed.
[0377] Regarding G-3 and U-2, it is believed that due to the excessively large bending radius in aging treatment 1, sufficient tensile strain was not generated to promote the formation of clusters or transition carbides. As a result, a sufficient amount of ε-carbides could not precipitate in aging treatment 1, and the difference in the number density of precipitates in the tempered martensite on the surface and back of the steel plate became large, failing to ensure sufficient bending resistance.
[0378] Regarding M-3, it is believed that due to the excessively large bending radius in aging treatment 2, insufficient tensile strain was generated to promote the formation of clusters or transition carbides. As a result, a sufficient amount of ε-carbides could not precipitate in aging treatment 2, and the difference in the number density of precipitates in the tempered martensite on the surface and back of the steel plate became large, failing to ensure sufficient bending resistance.
[0379] Regarding N-3 and AF-2, due to the short aging time in aging treatment 2, the difference in the amount of precipitates precipitated in aging treatment 1 and aging treatment 2 becomes larger. As a result, the difference in the number density of precipitates in the tempered martensite on the surface and back of the steel plate becomes larger, and the bending resistance of the steel plate decreases.
[0380] Regarding K-4 and AW-4, since at least one of aging treatments 1 and 2 is omitted, the number density of precipitates in tempered martensite in at least one of the surface and back surfaces of the steel plate is not controlled, resulting in a larger difference in the number density of precipitates in tempered martensite in the surface and back surfaces of the steel plate. As a result, the bending resistance of the steel plate decreases.
[0381] In contrast, regarding examples other than those mentioned above, by manufacturing steel sheets with a specified chemical composition under specified conditions, a specified metallic structure is obtained in the steel sheets, and the steel sheets exhibit excellent formability and bending resistance. Furthermore, regarding the steel sheet obtained in Example 2, which has undergone aging treatment and contains tempered martensite, the precipitate number density is 1 precipitate / μm. 2 ~300 cells / μm 2 Within the range.
[0382] Based on the above results, it can be said that steel plates that meet the following necessary conditions (I) to (IV) have excellent mechanical properties such as strength and elongation, and also have excellent bending resistance.
[0383] (I) The steel plate has the following chemical composition (by mass%): C: 0.10–0.30%, Si: 0.60–1.20%, Mn: 1.00–3.50%, P: less than 0.0200%, S: less than 0.0200%, Al: 0.001–1.000%, N: less than 0.0200%, Ti: 0–0.500%, Co: 0–0.500%, Ni: 0–0.500%, Mo: 0–0.500%, Cr: 0–2.000%, O: 0–0.0100%, B: 0–0.01%. 0.00%, Nb: 0-0.500%, V: 0-0.500%, Cu: 0-0.500%, W: 0-0.1000%, Ta: 0-0.1000%, Sn: 0-0.0500%, Sb: 0-0.0500%, As: 0-0.0500%, Mg: 0-0.0500%, Ca: 0-0.0500%, Y: 0-0.0500%, Zr: 0-0.0500%, La: 0-0.0500%, and Ce: 0-0.0500%, with the remainder consisting of Fe and impurities.
[0384] (II) The steel plate has the following steel structure: comprising, by area ratio: 0% to 30.0% of ferrite, pearlite and bainite, and 10.0% to 30.0% of retained austenite, with the remainder being martensite and tempered martensite.
[0385] (III) The difference between the number density of precipitates in the tempered martensite on the first surface of the steel plate and the number density of precipitates in the tempered martensite on the second back surface of the steel plate is within 10.0%.
[0386] (IV) The yield strength of the steel plate is above 600 MPa.
[0387] Furthermore, steel plates that meet the above-mentioned necessary conditions (I) to (IV) can be manufactured by the following methods.
[0388] A method for manufacturing a steel plate, comprising the following steps:
[0389] A hot-rolled plate is obtained by hot rolling a steel slab having the above-mentioned chemical composition (I);
[0390] The hot-rolled sheet is then coiled.
[0391] The hot-rolled plates were pickled.
[0392] The above-mentioned hot-rolled sheet is cold-rolled to obtain a cold-rolled sheet;
[0393] The above-mentioned cold-rolled sheet was subjected to Q annealing;
[0394] The cold-rolled sheet subjected to the above Q annealing is then subjected to IA annealing; and
[0395] An aging process is performed between the Q-annealing and the IA-annealing described above.
[0396] The Q annealing described above is a process in which the cold-rolled sheet is heated to a temperature below 1000°C in the austenitic single-phase region and then cooled to obtain a martensitic structure with an area ratio of 90.0% or more.
[0397] The aforementioned IA annealing is a process in which the cold-rolled sheet is held in a two-phase region of ferrite and austenite to obtain retained austenite.
[0398] The aforementioned aging treatment includes: aging treatment 1, which maintains the state in which one of the front and back sides of the cold-rolled sheet is subjected to tensile deformation with a bending radius of less than 2.0m at 0 to 40°C for a period of 20 hours or more; and aging treatment 2, which maintains the state in which the other side of the front and back sides of the cold-rolled sheet is subjected to tensile deformation with a bending radius of less than 2.0m at 0 to 40°C for a period of 20 hours or more.
Claims
1. A steel plate having the following chemical composition: containing, by mass %: C:0.10~0.30%、 Si: 0.60–1.20% Mn: 1.00~3.50%, P: Below 0.0200% S: Below 0.0200% Al:0.001~1.000%、 N: below 0.0200% Ti: 0~0.500%, Co: 0~0.500%, Ni: 0~0.500%, Mo: 0~0.500%, Cr:0~2.000%、 O:0~0.0100%、 B:0~0.0100%、 Nb: 0~0.500%, V:0~0.500%、 Cu: 0~0.500%, W:0~0.1000%、 Ta: 0~0.1000% Sn: 0~0.0500% Sb: 0~0.0500%, As: 0~0.0500%, Mg: 0~0.0500%, Ca: 0~0.0500%, Y:0~0.0500%、 Zr:0~0.0500%、 La: 0~0.0500%, and Ce: 0~0.0500% The remaining part consists of Fe and impurities. The steel plate has the following steel structure, comprising, in terms of area ratio: The total of ferrite, pearlite, and bainite: 0%–30.0%, and Residual austenite: 10.0%–30.0% The remaining portion is formed from primary martensite and tempered martensite. The difference between the number density of precipitates in the tempered martensite on the first surface of the steel plate and the number density of precipitates in the tempered martensite on the second back surface of the steel plate is within 10.0%. The yield strength of the steel plate is above 600 MPa.
2. The steel plate according to claim 1, having a chemical composition comprising, by mass percent, one or more of the following elements: Ti: 0.001~0.500%, Co: 0.001~0.500%, Ni: 0.001~0.500%, Mo: 0.001~0.500%, Cr:0.001~2.000% O:0.0001~0.0100% B:0.0001~0.0100%、 Nb: 0.001~0.500%, V:0.001~0.500%、 Cu: 0.001~0.500%, W:0.0001~0.1000%、 Ta: 0.0001~0.1000% Sn: 0.0001~0.0500% Sb: 0.0001~0.0500% As: 0.0001~0.0500% Mg: 0.0001~0.0500%, Ca: 0.0001~0.0500%, Y:0.0001~0.0500%、 Zr:0.0001~0.0500%、 La: 0.0001~0.0500%, and Ce: 0.0001~0.0500%.
3. The steel plate according to claim 1 or 2, wherein, The steel microstructure comprises needle-like retained austenite.
4. A method for manufacturing the steel plate according to claim 1 or 2, comprising the following steps: A hot-rolled plate is obtained by hot rolling a steel slab having the chemical composition described in claim 1 or 2; The hot-rolled sheet is rolled up; The hot-rolled plate is pickled. The hot-rolled sheet is cold-rolled to obtain a cold-rolled sheet; The cold-rolled sheet is subjected to Q annealing; The cold-rolled sheet subjected to the Q annealing is then subjected to IA annealing; and An aging process is performed between the Q-annealing and the IA-annealing. The Q annealing is a process in which the cold-rolled sheet is heated to a temperature below 1000°C in the austenitic single-phase region and then cooled to obtain a martensitic structure with an area ratio of 90.0% or more. The IA annealing process involves holding the cold-rolled sheet in a two-phase region of ferrite and austenite to obtain retained austenite. The aging treatment includes: aging treatment 1, which maintains the cold-rolled sheet in a state of being subjected to tensile deformation with a bending radius of less than 2.0 m on one side of the front and back sides for a period of more than 20 hours at 0 to 40°C; and aging treatment 2, which maintains the cold-rolled sheet in a state of being subjected to tensile deformation with a bending radius of less than 2.0 m on the other side of the front and back sides for a period of more than 20 hours at 0 to 40°C.
5. The manufacturing method according to claim 4, wherein, In the IA annealing, during the process of cooling the cold-rolled sheet to room temperature after holding it in the two-phase region of ferrite and austenite, a coating layer containing zinc, aluminum, magnesium or alloys thereof is formed on the front and back surfaces of the cold-rolled sheet.
6. The manufacturing method according to claim 4 or 5, wherein, In the IA annealing, needle-like residual austenite is obtained.
Citation Information
Patent Citations
High-strength thin steel sheet and method for manufacturing the same
JP2021025094A
High-strength steel sheet and method for manufacturing same
WO2020158065A1